STUDY OF UTILIZATION VETIVER SOLID WASTE AS FUEL SUBSTITUTION IN ESSENTIAL OIL DISTILLATION PROCESS - Chalida Yasmin, Jihan
Vetiver (Chrysopogon zizanioides) is a plant that can produce essentials oil through distillation process. The distillation process produces vetiver solid waste that can reach 98.8% of mass from its raw material, hence it needs a lot of space for storage. In this research, vetiver solid waste is processed so that it can be utilized as solid fuel for essentials oil distillation and liquid fertilizer. In this research, wet torrefaction process was employed to convert the vetiver waste intu usable fuel using water as medium at varied temperature of 150 to 200°C, with 30 and 90 minutes of holding time. Solid products of wet torrefaction were analysed in the aspect of density, high heating value (HHV), energy density, and mass yield as solid fuel, while the liquid products were analysed from its nitrogen, phosphorous, and potassium (NPK) content as liquid fertilizer. The results of experiments showed that wet torrefaction of vetiver waste in high temperature increased the density and HHV of the solid products, therefore energy density also increased. However, the self sustainability of the process was low due to the high requirement of energy. NPK content in liquid products were similar to NPK content in liquid fertilizer available in the market, however it was below the standard from Ministry of Agriculture. Therefore, vetiver waste was better utilized as solid fuel directly with shredding to increase the density. The fuel of distillation process can be replaced with used oil and vetiver waste ratio of 1:4. Vetiver waste that can be utilized as solid fuel was 76.98% of total waste produced from distillation process. The 23.02% remainder can be utilized as air freshener in the form of briquette because vetiver waste still contained 0.12% essential oil after the distillation process.